The Impact of Financial Literacy and Fintech Adoption on Personal Financial Management Among University Students - Kurniawan, Mochamad Riski Fajar; Retnasih, Nora Ria (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2024)
This study aims to examine the influence of financial literacy and fintech adoption on personal financial management among students at UIN Malang. This quantitative research involved 155 students from the Management Department, class of 2022, as the sample. Data collection was conducted through an online questionnaire distributed via Google Forms and analyzed using multiple linear regression with the help of IBM SPSS Statistics 23 software. The results show that financial literacy has a significant positive impact on students' personal financial management. Furthermore, the adoption of financial technology also has a significant positive impact on students' personal financial management. These findings suggest that both financial literacy and fintech adoption play crucial roles in enhancing students' ability to manage their finances effectively. The study underscores the importance of promoting financial literacy and the use of fintech among students to foster better financial management practices. Future research should explore other factors that may influence personal financial management and investigate the long-term effects of financial literacy and fintech adoption on financial behavior.